A Coach-Delivered Dating Violence Prevention Program: Coach Perspectives on Implementation. Issue 13 (July 2022) - Fields, Alana D.; Fenn, Mikaela; Ripper, Lisa; Hill, Ashley; Mulbah, Paul; Kass, Nicolás Matheo; Miller, Elizabeth
Coaching Boys into Men (CBIM), an evidence-based violence prevention program, utilizes the coach-athlete relationship to deliver information about healthy, respectful relationships to adolescent boys involved in athletics. Although CBIM has demonstrated effectiveness in clinical research trials, its implementation outside of an effectiveness study has not been explored. The purpose of this current study was to explore facilitators and barriers of effective implementation in community settings using experiences from one regional implementation in Southwestern Pennsylvania. Head coaches who implemented CBIM from 2017-2018 seasons ( n = 35) were contacted and 22 (63%) agreed to participate. Coaches were asked how they delivered CBIM to their team, what aided the process, barriers to facilitation, and their overall thoughts on CBIM implementation. Interviews were structured to uncover specific information regarding implementation while also providing time and space for coaches to voice their suggestions and opinions. Interviews were coded using descriptive content analysis. Key facilitators to implementation were involvement of violence prevention advocates, athletic directors, assistant coaches, and players and having flexibility to integrate current events to emphasize topics covered in CBIM. Observed improvements in bystander intervention behaviors and better attitudes towards women and girls among athletes were key motivators for coaches to continue the program. Main barriers were inconsistencies in time available to discuss topics with players and need to refresh curriculum content over multiple seasons. Coaches identified components necessary for broader and sustained implementation of this evidence-based violence prevention intervention in community settings. Coaches' confidence in delivering program content can be bolstered with appropriate strategies in place to address barriers. As coaches witness positive impacts among their athletes, these successes contribute to coaches recognizing their role in transforming sports into a platform for community-wide violence prevention.